Impacto de las plagas en el rendimiento del fréjol phaseolus vulgaris l. - Ramírez Criollo, Santiago Fabián (2010)
Research on the impact of pests on the yield of beans (Phaseolus vulgaris L.) was conducted at the Faculty of Agricultural Sciences at the Technical University of Machala, of the Parroquia The Cambio during the months of September to November of 2009 and studied the agronomic performance of four varieties of bean (Phaseolus vulgaris L.) to attack without pest control, the objectives of this study were: 1. To estimate the impact of pests on yield of four varieties of beans, 2. Determine which variety is more susceptible to pest attack, and 3. Perform an economic analysis of the project.. The varieties studied were: Mantequilla, Boca Negra, Cocacho and Vilcabamba, the respective seeding was conducted along the lines of random block design. Seedlings emerged after five to six days after sowing, which then made all the work required of the crop. The variables analyzed were: number of leaflets affected plant height at 30, 60 and at harvest, percentage of affected flowers, percentage of pods affected, affected number of pods, 100 seed weight, yield per hectare. The analysis of variance and Duncan test for the averages of treatments showed a high significance for the variances of the treatments on all agronomic traits. The bush varieties were the earliest to the production, while the semi-shrub was the later. Introduced varieties such as Vilcabamba and Cocacho and obtained good results in terms of production, profits and were resistant to pests in the middle. From the standpoint of the variety Mantequilla, the production was an average yield of 973.99 kg / ha, Boca Negra had the highest average yield of 6079.89 kg / ha, Cocacho obtained an average yield of 1677.01 kg / ha and Vilcabamba obtained an average yield of 1245.08 kg / ha. The variety most affected in the development stage was the Mantequilla as well as the Boca Negra and was also involved in the production stage.